A systematic review of factors influencing treatment adherence in chronic inflammatory skin disease – strategies for optimizing treatment outcome. (14th November 2019) - Eicher, L.; Knop, M.; Aszodi, N.; Senner, S.; French, L.E.; Wollenberg, A.
Abstract: Adherence describes how a patient follows a medical regime recommended by a healthcare provider. Poor treatment adherence represents a complex and challenging problem of international healthcare systems, as it has a substantial impact on clinical outcomes and patient safety and constitutes an important financial burden. Since it is one of the most common causes of treatment failure, it is extremely important for physicians to reliably distinguish between non‐adherence and non‐response. This systematic review aims to summarize the current literature on treatment adherence in dermatology, focusing on chronic inflammatory skin diseases such as psoriasis, atopic dermatitis and acne. A systematic literature search was performed using the PubMed Database, including articles from 2008 to 2018. Low treatment adherence is a multidimensional phenomenon defined by the interplay of numerous factors and should under no circumstances be considered as the patient's fault alone. Factors influencing treatment adherence in dermatology include patient characteristics and beliefs, treatment efficacy and duration, administration routes, disease chronicity and the disease itself. Moreover, the quality of the physician‐patient relationship including physician‐time available for the patient plays an important role. Understanding patients' adherence patterns and the main drivers of non‐adherence creates opportunities to improve adherence in the future. Strategies to increase treatment adherence range from reminder programs to simplifying prescriptions or educational interventions. Absolute adherence to treatment may not be realistically achievable, but efforts need to be made to raise awareness in order to maximize adherence as far as possible.